PENGELOLAAN KEUANGAN BERKELANJUTAN DI KABUPATEN BLITAR MELALUI PENDEKATAN GREEN BUDGETING - Susilo; Al Muizzuddin Fazaalloh; Roekhuddin; Afif Khoiruddin; Alvira 'Aina A'yun (Jurnal Berdaya Mandiri, 2026)
Sustainability issues in village financial governance have become increasingly important amid growing demands for environmentally sound and inclusive development. Srengat Subdistrict, Blitar Regency, has significant economic potential based on agriculture and micro, small, and medium enterprises (MSMEs). However, village budgeting practices remain largely focused on physical and administrative expenditures, with limited consideration of social and environmental impacts. This community service program aims to enhance the capacity of village officials and local economic actors in implementing sustainable financial management through the integration of green budgeting principles into the Village Revenue and Expenditure Budget (APBDes). The program adopted a Participatory Action Research (PAR) approach, including socialization, training, the application of matrix-based Green Tagging, and three months of mentoring and evaluation. Initial assessments revealed low sustainable finance literacy, the absence of Green Tagging practices, and the lack of technical guidelines for classifying green activities at the village level. Preliminary results demonstrate improved understanding of green budgeting, the development of a draft green activity classification toolkit compatible with the village financial system, and the establishment of a Green Budgeting Working Group. This initiative marks an important step toward transparent, participatory, and triple bottom line–oriented village financial governance. Keywords: Sustainable Finance; Village Government; Green Budgeting